Preliminary Performance Tests and Simulation of a V-Shape Roof Guide Vane Mounted on an Eco-Roof System - Wang, Xiao Hang; Chong, Wen Tong; Wong, Kok Hoe; Saw, Lip Huat; Poh, Sin Chew; Lai, Sai Hin; Wang, Chin Tsan (MDPI, 2018)
The technical and economic features of a patented V-shape roof guide vane (VRGV) with a solar and wind power generation system mounted on an eco-roof system are presented in this paper. Moreover, this innovative VRGV was investigated on for the purpose of improving the performance of a vertical axis wind turbine (VAWT), which was installed on an eco-roof system to solve the low-efficiency power generation problem of the wind turbines under the condition of a low wind speed. This paper proposes a preliminary study for the performance of the VAWT with the VRGV on a building. This research used a mock-up building with a double slope roof, where a five straight-bladed VAWT was mounted and tested under two conditions, with and without the VRGV. From the comparative experiments, the self-starting performance and rotational speed of the VAWT mounted above a double slope roof with the VRGV have been significantly improved compared to the VAWT without the VRGV. Further, the power coefficient (Cp) of the VAWT can be augmented to about 71.2% increment due to the VRGV design. In addition, numerical simulations by computational fluid dynamics (CFD) were proposed to verify the augmented effect of the Cp of the VAWT under the influence of the VRGV in the experiment. Besides, economic estimation of the VRGV was conducted.